Inactivation of DNA Mismatch Repair by Variants of Uncertain Significance in the PMS2 Gene. Issue 11 (11th September 2013) - Drost, Mark; Koppejan, Hester; de Wind, Niels
Abstract : The cancer predisposition Lynch syndrome is diagnosed by the identification of a disruptive mutation in one of the DNA mismatch repair genes. Unfortunately, the identification of a variant of uncertain significance frequently precludes diagnosis, which interferes with clinical management. Here we use a rapid and cell‐free assay to test functional activity of nearly all variants identified to date in PMS2, revealing loss of activity for five variants. This assay may greatly facilitate the diagnostic assessment of PMS2 variants. ABSTRACT: Lynch syndrome (LS) is a common cancer predisposition caused by an inactivating mutation in one of four DNA mismatch repair (MMR) genes. Frequently a variant of uncertain significance (VUS), rather than an obviously pathogenic mutation, is identified in one of these genes. The inability to define pathogenicity of such variants precludes targeted healthcare. Here, we have modified a cell‐free assay to test VUS in the MMR gene PMS2 for functional activity. We have analyzed nearly all VUS in PMS2 found thus far and describe loss of MMR activity for five, suggesting the applicability of the assay for diagnosis of LS.